Anti-thrombotic therapy in non-ST elevation acute coronary syndrome KAA Fox - Fox, Keith A.A. (SA Heart Journal, 2017)
Platelet activation and thrombin generation are implicated in the pathogenesis of acute coronary syndrome, in the development of major thrombotic complications of the condition, and in the interventional treatments to treat obstructive coronary lesions (principally, percutaneous coronary intervention). Despite treatment with aspirin and heparin there remained a clinically important risk of thrombotic complications both in hospital and following discharge. Newer anti-platelet therapies (thienopyridines and glycoprotein IIb/IIIa inhibitors) reduced platelet mediated complications, but with an increase in bleeding risk. Similarly, low molecular weight heparins reduced thrombotic complcations but with a modest increase in bleeding. Newer anti-thrombins (anti Xa inhibitors and direct thrombin inhibitors) demonstrate similar or improved efficacy, but with reduced bleeding. Insufficient attention has been paid to reducing bleeding complications and recent evidence suggests that major bleeding conveys a significant increase in the risk of death. In addition, clearance of antithrombotic agents by the kidney is impaired in those with renal dysfunction, including in the elderly, and this may contribute to the risks of bleeding. In unselected populations with non-ST elevation ACS more than half the population have a creatinine clearance below 60 ml/min. Reducing the doses of anti-thrombins in patients with renal dysfunction may reduce bleeding complications. The optimal anti-thrombotic strategy in patients with non-ST elevation ACS requires the clinician to consider not only the risk of the patient for thrombotic complcations, but also the hazards of bleeding. Newer anti-thrombotic agents, for the first time, offer potential benefits in bleeding risk with similar or improved efficacy.